2001
DOI: 10.1002/path.966
|View full text |Cite
|
Sign up to set email alerts
|

Liver metastases from colorectal adenocarcinomas grow in three patterns with different angiogenesis and desmoplasia

Abstract: The liver is a highly vascularized organ which frequently hosts metastases in patients with colorectal adenocarcinomas. The hypothesis of this study is that the hypoxic drive of angiogenesis might be minimal or absent in those growing liver metastases which are capable of preserving the stromal structure, including the numerous sinusoidal blood vessels. Representative paraffin sections of liver metastases from 26 patients with colorectal adenocarcinoma were investigated. Three different growth patterns were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
224
3
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 259 publications
(252 citation statements)
references
References 16 publications
10
224
3
2
Order By: Relevance
“…4e). Analysis of human cancers reveals vessel co-option in glioblastoma [182, 183], adenocarcinoma of the lung [184, 185] cutaneous melanoma [186], lung metastases of breast and renal cancer [187–189], liver metastases of colorectal and breast cancer [190, 191] and brain metastases of lung and breast cancer [192]. …”
Section: Mechanisms Of Response and Resistance To Vegf-targeted Therapymentioning
confidence: 99%
“…4e). Analysis of human cancers reveals vessel co-option in glioblastoma [182, 183], adenocarcinoma of the lung [184, 185] cutaneous melanoma [186], lung metastases of breast and renal cancer [187–189], liver metastases of colorectal and breast cancer [190, 191] and brain metastases of lung and breast cancer [192]. …”
Section: Mechanisms Of Response and Resistance To Vegf-targeted Therapymentioning
confidence: 99%
“…In other words, this observation indicated that tumor vessels in the high MVD tumors consisted of a higher percentage of mature tumor vessels than those in the low MVD tumors. On the other hand, Vermeulen et al [16] demonstrated that in liver metastases from colorectal cancers, the fraction of immature microvessels correlated strongly with the MVD. Kakolyris et al [17, 18] also reported a significant association between a high vascular maturation index and a low microvessel score in non-small-cell lung carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of dependence on vascularisation of growth, invasion and metastasis of malignant tumours has been challenged by the description of angiogenesis-independent mechanisms [7-10]. Nevertheless, the growth of most primary tumours needs angiogenesis.…”
Section: Introductionmentioning
confidence: 99%